WHETHER THE STUDY ON EFFICACY OF ROSUVASTATIN IN ELDERLY PATIENTS WITH HEART FAILURE AND SYSTOLIC DYSFUNCTION OF LEFT VENTRICLE HAD BEEN COMPLETED WITH “CROWNING”? - S. R. Gilyarevsky (Рациональная фармакотерапия в кардиологии)
Whether the study on efficacy of rosuvastatin in elderly patients with heart failure and systolic dysfunction of left ventricle had been completed with “crowning”?